Pengetahuan Epistemik Siswa SMP di Medan pada Materi Krisis Energi - Tariza Fairuz; Nadia Mubarokah; Sri Masnita Pardosi (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
This study aims to measure and describe the level of epistemic knowledge of junior high school students in Medan City on the subject of energy crisis. The research approach uses a descriptive quantitative method with a sample of 92 ninth-grade students selected through cluster random sampling. Data were collected using a 15-item essay test that had been validated and proven reliable. Data analysis was performed using descriptive statistics through the calculation of average scores, frequency distribution, and the percentage of achievement for each epistemic aspect. The results showed that the students' level of epistemic knowledge was in the moderate category with an average of 58%, indicating that their understanding of how science works, especially on the issue of energy crisis, was not yet optimally developed. These findings emphasize the need for a learning model that places greater emphasis on evidence-based argumentation, the use of scientific models, and the exploration of the nature of science. Further research is recommended to integrate inquiry-based learning designs to test the effectiveness of interventions in improving students' epistemic knowledge.